Learning obstacles analysis of lowest common multiple and greatest common factor in primary school - Muhammad Rifqi Mahmud; Turmudi Turmudi; Wahyu Sopandi; Siti Maryam Rohimah; Inne Marthyane Pratiwi (Universitas Hamzanwadi, 2023)
This research aims to find learning obstacles for students studying LCM and GCF as a reference in preparing teaching materials that can overcome these obstacles. This research involved 74 grade V students at three public schools in Bandung, Indonesia. The research method used in this study was case study research—data collection techniques using triangulation by providing tests, interviews, and documentation. Data analysis techniques use data collection, reduction, presentation, and conclusions. The results show three categories of learning obstacles: ontogenic, epistemological, and didactic. The ontogenic obstacle was found because the students understood multiples, factors, and arithmetic operations on natural numbers in solving LCM and GCF problems. Epistemological obstacles were discovered because of the limited context in which students understood the concepts of LCM and GCF, so they could not use them in contexts such as word problems. Didactical obstacles were found from learning that was given by the teacher procedurally using factoring methods, namely prime factorization or factor trees. Therefore, these obstacles must be anticipated by designing learning designs that can facilitate learning trajectories, focus on concepts, and make learning more meaningful.